Carbon dioxide sequestration of fly ash alkaline-based mortars containing recycled aggregates and reinforced by hemp fibers: Mechanical properties and numerical simulation with a finite element method - Mastali, Mohammad (2018)
Natural fibers are a sustainable and renewable resource available almost all over the world having the advantage of being able to sequestrate atmospheric CO2 through photosynthesis. Being cost-effective and as stronger as synthetic fibers, they are of interest for the production of reinforced cementitious composites for the construction industry. This chapter discloses results of an investigation concerning the performance of fly ash/waste glass alkaline-based mortars with recycled aggregates reinforced by hemp fibers exposed to accelerated carbon dioxide curing. Compressive strength, flexural strength, and numerical simulations with a finite element method were studied on it.